Study of the Influence of Numerical and Physical Parameters on the Axial Thrust of Radial Machines - Vioulac, Cyril (My University, 2014)
As a sustainable and well-proven technology, hydroelectricity is widespread all over the world. The goal of the in here presented study is to assess the capacity of Computational Fluid Dynamics (CFD) to predict the axial thrust arising in a radial hydraulic machine. These devices are also called hydraulic pumps or turbines and consist of a rotating and a stationary part called runner and stator, respectively. The spaces between theses two di erent parts in the axial direction are known as side chambers. One side chamber is on the upper part of the runner while the other is on the bottom. The axial thrust is a residual force occurring in the machine, more precisely in the runner, which arises mainly due to pressure imbalance in the axial direction. This study proposes to focus on the pressure eld in the side chambers to amount the axial thrust. In addition, the axial force due to the static pressure and the impulse force of the ow applied on the runner are also taken into account. The particularity of this study is to focus on the ow eld in the side chambers, while these regions are disregard in a standard design process. For this purpose, a complete three-dimensional model of a turbine is made. The mesh is realized using ANSYS-ICEM-CFD. Then, di erent CFD simulations are performed using the commercial software ANSYS-CFX. Steady and unsteady simulations with steady and unsteady boundary conditions, respectively, have been made to calculate the axial thrust.
Keywords: Strömningsmekanik; Hållbar utveckling; Energi; Fluid mechanics; Sustainable Development; Energy